Accountable Care Organizations: Impact on Pharmacy. Issue 3 (March 2014) - Amara, Shilpa; Adamson, Robert T.; Lew, Indu; Slonim, Anthony
The Patient Protection and Affordable Care Act (PPACA) has considerably transformed the approaches being used to deliver health care in the United States. It was enacted to expand health insurance access, improve funding for health professions education, and reform patient care delivery. The traditional fee-for-service payment system has been criticized for overspending and providing substandard quality of care. The Accountable Care Organization (ACO) was developed as a payment reform mechanism to slow rising health care costs and improve quality. Under this concept, networks of clinicians and hospitals share responsibility for a population of patients and are held accountable for the financial and clinical outcomes. Due to high rates of medication misuse, nonadherence to therapeutic medication regimens, and preventable adverse drug events, pharmacists are in an ideal position to manage drug therapy and reduce health care expenditures; as such, they may be valuable assets to the ACO team. This article discusses the role of the pharmacist in the era of ACOs specifically and health care reform globally. It outlines pharmacy-related quality of care measures, medication therapy management (MTM) programs (which may provide the foundation for pharmacist involvement in ACOs), and pharmacist functions in patient-centered medical homes (through which ACO services may be organized). The article concludes with a description of successful ACO models that have incorporated pharmacists into their programs.